Analysis Of Rolling Contact - Malik, Muhammad Abdul Qahhar Abdul (Universiti Sains Malaysia, 2017)
In mechanical engineering and tribology, Hertzian contact stress is a description of the stress within mating parts. This kind of stress may not be significant most of the time, but may cause serious problems if not take it into account in some cases. An ideal bearing surface is the one with smooth surface and having relatively deep scratches to hold and distribute lubricant. The arithmetic average of the absolute value (Ra) and bearing area curve (BAC) had been recognise as better way to characterise 304SS roller surface. Deformation on the rolling surface can be reduced by applied low viscosity lubricant. Roughness value will increase as the number of cycles increase. The test have been conducted in two conditions (dry and lubricated) and endure one hundred cycles each. The two surface parameters with the highest value are average roughness Ra (0.7101μm) and bearing area curve (16.2656μm). Both results from dry condition